PRODUKSI BIOFUNGISIDA BERBAHAN BAKU MIKROBA ANTAGONIS INDIGENOUS UNTUK PENGENDALIAN PENYAKIT HAWAR DAUN TANAMAN KENTANG DI PROVINSI JATENG - Susiana Purwantisari; Achmadi Priyatmojo; Budi Raharjo (JURNAL LITBANG PROVINSI JAWA TENGAH, 2009)
Biological control of plant pathogens is an attractive alternative of the strong dependence of modern agriculture on chemical fungicides, which cause environmental pollution and development of resistant strains. Species of Trichoderma have long been known for their capacity to reduce plant diseases caused by fungal pathogens and some have been tested for biological control potential in many field and greenhouse trials. Late blight deseases is one of the most important deseases of Potato Plant which distributes almost all over high humidity region in Central Java. The aim of this research was to produce mass fungus antagonist Trichoderma sp. isolate inexpensive cost. The exact nature of this relationship is still not clear, but it appears that they kill other fungi with a toxin and then consume them using a combination of lytic enzymes. This suggests that they are actually microbial predators. This antagonistic behaviour has led to their use as agents of biological control of some fungi causing plant disease. Agricultural waste is the best choice to packing biofungicide formulation based on antagonist fungus of isolate Trichoderma sp. isolate. The study showed that the biofungicide production using local Trichoderma sp. isolate can be done in simple procedure using local agriculture waste. The biofungicide is considered safe and its production process can be socialized to control Lodoh desease presence in potatoes production areas.